Genetic and symptomatic characterization of sugarcane mosaic virus (SCMV) in Cuba - Puchades, Yaquelin (2017)
Sugarcane mosaic resistance is established as a key criterion for the breeding program in Cuba. However, molecular characterization of Sugarcane mosaic virus (SCMV) strains occurring in Cuba has not been reported so far. Leaf samples from commercial sugarcane cultivars were collected for SCMV screening in three testing sites (the Matanzas, Camagüey and Holguin provinces). Reverse-Transcriptase polymerase chain reaction was used to identify the virus. The nucleotide sequence comparison grouped the isolates into SCMV subgroups. Sugarcane cultivars inoculated with SCMV from three testing sites displayed different symptoms. Results should be decisive to generate the highest selection pressure, increasing the efficiency of the sugarcane breeding program to the SCMV resistance in the commercial cultivars.